Enhanced MPC for Fast Frequency Control in Inverter-Dominated Power Systems - Stanojev, Ognjen; Markovic, Uros; Vrettos, Evangelos; Aristidou, Petros; Callaway, Duncan; Hug, Gabriela (My University, 2020)
Due to the rising shares of renewable energy sources, future power systems are facing significant changes in control complexity and system inertia, thus making frequency regulation in power systems more challenging. This paper proposes a novel control scheme based on model predictive control for grid-forming Voltage Source Converters (VSCs), with the goal of exploiting their fast response capabilities and available DC-side energy storage to provide fast frequency control service to the system. An observer based on support vector machine regression detects and estimates system disturbances using only locally available measurements at each VSC. Frequency evolution is then anticipated through state-space predictions and the VSC power output is adjusted to compensate the disturbance and prevent frequency threshold violations. The proposed control scheme is evaluated and its effectiveness demonstrated through detailed time-domain simulations of the IEEE 39-bus test system.
Keywords: Model predictive control; Voltage source converter; Frequency support; Low-inertia systems; Support vector regression